Agency Theory Perspective on Dividend Policy - Mursyidin, Mursyidin (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to review the literature on dividend policy from the perspective of agency theory with a qualitative approach. The research object used was several research articles published in international journals in 2014–2022, and the sample used was 20 articles. The findings explain that share ownership structure, corporate governance, agency costs, free cash flow, profitability, and other financial performance and debt values are factors in determining dividend policy. A dividend policy can be used as a way to monitor opportunistic behavior and as a tool to reduce agency problems.